Interaksi Pengetahuan dan Perceived Severity Kanker Serviks dengan Perilaku Pemilihan Pembalut Mahasiswi - Ambar Sulianti; Shofa Mutiara Arafah (Psympathic : Jurnal Ilmiah Psikologi, 2019)
Indonesia is the country with the highest number of cervical cancer sufferers in the world. Although the use of sanitary pads containing harmful whitening agents has been known as one of the predispositions of cervical cancer, the rate of cervical cancer continues to increase. This study aims to analyze the relationship between knowledge and perceived severity of cervical cancer with the behavior of choosing sanitary napkin in college students. This study used a quantitative method of cross-sectional study on 125 research subjects. The results showed that there were no significant differences in the selection of pads both in the knowledge of high and low cervical cancer. However, there is interaction between high knowledge and high perceived severity on sanitary pads selection.